Endophthalmitis Prophylaxis in Cataract Surgery: Overview of Current Practice Patterns Around the World - Grzybowski, Andrzej; G. Schwartz, Stephen; Matsuura, Kazuki; O. Tone, Stephan; Arshinoff, Steve; Q. Ng, Jonathon; J. Meyer, Jay; Liu, Wu; Jacob, Soosan; Packer, Mark; Lutfiamida, Rifna; Tahija, Sjakon; et al. (Current Pharmaceutical Design, 2017)
Background: Acute-onset postoperative endophthalmitis after cataract surgery remains a rare but important cause of visual loss. There is no global consensus regarding the optimal strategies for prophylaxis of endophthalmitis and practices vary substantially around the world, especially with respect to the use of intracameral antibiotics. The European Society of Cataract & Refractive Surgeons in a randomized clinical trial (2007) reported an approximately 5-fold reduction in endophthalmitis rates associated with the use of intracameral cefuroxime. Despite this report, the use of intracameral antibiotics has not been universally adopted. Methods: Various endophthalmitis prophylaxis patterns around the world (including the United States, Canada, Australia/New Zealand, Japan, China, India, Indonesia, South Africa, Argentina, Russia, Sweden and Mexico) are compared. Each contributing author was asked to provide similar information, including endophthalmitis rates based on published studies, current practice patterns, and in some cases original survey data. Various methods were used to obtain this information, including literature reviews, expert commentary, and some new survey data not previously published. Results: Many different practice patterns were reported from around the world, specifically with respect to the use of intracameral antibiotics. Conclusion: There is no worldwide consensus regarding endophthalmitis prophylaxis with cataract surgery.
Keywords: intracameral antibiotics